Intuitionistic Fuzzy PRI-AND and PRI-OR Aggregation Operators Based on the Priority Degrees and Their Applications in Multi-Attribute Decision Making - Rui Hua (IEEE, 2021)
Multi-attribute decision making (MADM) problems that exist a prioritization relationship between the attributes get more and more scholars’ attention. Considering that the priority relationship of attributes, the concept of priority degree was applied to assign a non-negative real number to each priority order and such a non-negative real number is called the priority degree. In this paper, we introduce two new kinds of intuitionistic fuzzy prioritized aggregation operators based on the priority degrees: intuitionistic fuzzy prioritized “and” aggregation operators (PRI-AND) based on the priority degrees and intuitionistic fuzzy prioritized “or” aggregation operators (PRI-OR) based on the priority degrees and also establish some important properties of these aggregation operators in their different particular cases. Next, we develop a new method for addressing the multi-attribute decision making problems in which the attributes are in different priority levels based on intuitionistic fuzzy prioritized “or” aggregation operators based on the priority degrees. The new proposed methods can provide more choices for decision makers and many decision makers choose the appropriate priority degrees according to their own preference. Finally, an illustrative example is provided to prove the rationality of the proposed approach.